Penatalaksanaan Holistik Pasien Laki – Laki Usia 53 Tahun Dengan Low Back Pain dan Diabetes Melitus Tipe 2 Melalui Pendekatan Kedokteran Keluarga - Ahmad Zidane Sagareno; Tutik Ernawati (CV. Jasa Sukses Abadi, 2023)
Low back pain is pain in the lower back area caused by nerve problems, muscle irritation or bone lesions. In Indonesia, the prevalence of musculoskeletal diseases is 24.7 percent, while in Lampung province the prevalence of musculoskeletal diseases is 18.9 percent. The highest prevalence of musculoskeletal disease at work is a farmer, fisherman or laborer at 31.2 percent. At the initial treatment, a 53-year-old male patient was found with complaints of pain in the lower back. Primary data were obtained through interview, physical examination and home visits. Secondary data was obtained from the patient's medical records at the PUSKESMAS (Community Health Centre). Family doctor services are carried out to identify risk factors, clinical problems, as well as evidence-based medicine based patient management that is family-approach, patient-centered and community oriented. The assessment is carried out based on a holistic diagnosis of the initial, process, and final studies both quantitatively and qualitatively. In patients found comorbid Diabetes Mellitus Type 2. The interventions provided were in the form of medical and non-medical interventions related to the patient's disease. Medical intervention aims to minimize complaints and prevent complications in order to improve the patient's quality of life. Non-medical interventions in the form of patient and family education about disease risk factors, patient lifestyle, eating patterns, and physical activity. After the intervention, the visual analogue scale of pain (VAS) is decreased from six to one.